1988
DOI: 10.1128/aac.32.8.1154
|View full text |Cite
|
Sign up to set email alerts
|

New class of antifungal agents: jasplakinolide, a cyclodepsipeptide from the marine sponge, Jaspis species

Abstract: Jasplakinolide is a cyclodepsipeptide which represents a new class of antifungal agents with potent activity against Candida albicans. Jasplakinolide is fungicidal against C. albicans with both a MIC and a minimum lethal concentration of 25 >.g/ml in a broth dilution assay. This activity compares to that of the imidazole miconazole nitrate, which had a MIC of 6.2 ,ug/ml and a minimum lethal concentration of 50 ,ug/ml in the same assay. Topical administration of 2% jasplakinolide cream against a murine vaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 10 publications
3
55
0
Order By: Relevance
“…S6 in the supplemental material) isolated from sponge Jaspis sp. (71). This similarity suggests a shared underlying structure of biosynthetic proteins and/or gene clusters.…”
Section: Discussionmentioning
confidence: 97%
“…S6 in the supplemental material) isolated from sponge Jaspis sp. (71). This similarity suggests a shared underlying structure of biosynthetic proteins and/or gene clusters.…”
Section: Discussionmentioning
confidence: 97%
“…compounds isolated from sponges are the chondramides [18], which resemble jaspamide/jasplakinolide from the sponge Jaspis johnstoni [19], and saframycin [20] which is chemically related to renieramycin from the sponge Reniera sp. [21].…”
Section: Biological Propertiesmentioning
confidence: 99%
“…7A). To determine whether the increased adhesion requires reorganization of filamentous actin, we applied the cell permeable reagent jasplakinolide, which stabilizes actin filaments (Scott et al, 1988;Visegrady et al, 2005), and found that pretreatment with jasplakinolide reduced adhesion to netrin 1 and blocked the effects of inhibiting RhoA signaling (Fig. 7A).…”
Section: Research Articlementioning
confidence: 99%